Refugiados congoleses na cidade de São Paulo: processo migratório e itinerários terapêuticos - Haydu, Marcelo [UNIFESP] (2017)
In the context of migrants in search of refuge, the experiences reported in both the country of origin and destination involve elements with the potential of triggering suffering in those people seeking refuge. The displacement in search of refuge may compromise the health of those people. This research project aims to look into the therapeutic itineraries for the preservation and recovery of the health of the refugees who come from the Democratic Republic of the Congo, who are now residents of São Paulo. Fifteen in-depth interviews have been carried out with the Congolese people living here as refugees, as well as ethnographic observations. This research has shown that it is not possible to generalize about the health situation of the refugees. In spite of the fact that all the Congolese have reported cases of suffering, mainly due to the difficulties and adversities found in the places of refuge, the process of refuge has not been translated into cases of both physical and/or mental illnesses of great significance as a whole. Nonetheless, those people need a great deal of support in regard to their health situation as a result of the suffering they are invariably submitted to. The analysis of the itineraries has demonstrated that the paths taken by the Congolese in search of therapeutic care do not always coincide with predetermined schemes or influxes. Their choices express both individual and collective subjective constructions with regard to the process of falling ill and the methods of treatment, forged under the influences of various factors and contexts. As a whole, the paths taken by the Congolese encompass self-awareness, on a smaller scale, and the Brazilian Unified Health System (SUS), more significantly speaking, but above all, social networks (family and friends) and spirituality. It is worth pointing out that almost all of the interviewees do not have a full perception of their mental health in biomedical terms. The illness is not seen as a strictly biological/bodily process, but as a result of the cultural context and the subjective experience of feeling ill.